2013
DOI: 10.1136/thoraxjnl-2012-203029
|View full text |Cite
|
Sign up to set email alerts
|

Adverse respiratory effects associated with cadmium exposure in small-scale jewellery workshops in India

Abstract: Background Cadmium (Cd) is an important metal with both common occupational and environmental sources of exposure. Although it is likely to cause adverse respiratory effects, relevant human data are relatively sparse. Methods A cross-sectional study of 133 workers in jewellery workshops using Cd under poor hygienic conditions and 54 referent jewellery sales staffs was performed. We assessed symptoms, performed spirometry, measured urinary Cd levels in all study subjects and quantified airborne total oxidant co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 26 publications
2
38
0
2
Order By: Relevance
“…With chronic Cd-exposure, some reports have identified a strong exposure-response relationship for adverse respiratory effects [Davison et al, 1988;Nemery, 1990;Fuortes et al, 1991;Sorahan et al, 1995;Sorahan and Esmen, 2004;Fireman et al, 2008;Rokadia and Agarwal, 2013], while others have not [Chan et al, 1988;Jakubowski et al, 2004]. However, there are substantial reports, which have demonstrated adverse respiratory effects due to occupational cadmium exposure [Baker et al, 1979;Mason et al, 1999;Panchal and Vaideeswar, 2006;Sethi et al, 2006;Moitra et al, 2013]. Fireman et al [2008] observed that Cd-induced respiratory impairment involved elevated neutrophil infiltration in alveolar bed in induced sputum among a group of welders exposed to heavy metals.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…With chronic Cd-exposure, some reports have identified a strong exposure-response relationship for adverse respiratory effects [Davison et al, 1988;Nemery, 1990;Fuortes et al, 1991;Sorahan et al, 1995;Sorahan and Esmen, 2004;Fireman et al, 2008;Rokadia and Agarwal, 2013], while others have not [Chan et al, 1988;Jakubowski et al, 2004]. However, there are substantial reports, which have demonstrated adverse respiratory effects due to occupational cadmium exposure [Baker et al, 1979;Mason et al, 1999;Panchal and Vaideeswar, 2006;Sethi et al, 2006;Moitra et al, 2013]. Fireman et al [2008] observed that Cd-induced respiratory impairment involved elevated neutrophil infiltration in alveolar bed in induced sputum among a group of welders exposed to heavy metals.…”
Section: Introductionmentioning
confidence: 93%
“…The recruitment criteria of the participants in the main cohort have been reported elsewhere [Moitra et al, 2013]. 187 male participants were recruited from a preliminary screened pool of 276 workers of whom 133 were actively involved in jewelry manufacturing and 54 were unexposed referent workers (mainly sales persons) in the same industry.…”
Section: Study Populationmentioning
confidence: 99%
“…17 To subjectively asses respiratory health, participants were asked if they had experienced any of the following symptoms in the previous 12 months: prolonged cough, chronic phlegm, morning cough with sputum, acute or chronic wheezing or whistling in chest, breathing trouble, nasal allergy, and/or a runny or stuffed nose.…”
Section: Questionnaire Assessmentmentioning
confidence: 99%
“…The questionnaire was a modified version of the European Community Respiratory Health Survey-II (ECRHS-II) that has been used in prior studies. [17][18][19] Subjective respiratory complaints in the previous 12 months questioned were (1) acute or chronic wheezing or whistling of the chest, (2) tightness in chest, (3) breathing trouble, (4) acute or chronic cough, and (5) nasal allergy.…”
Section: Respiratory Questionnairementioning
confidence: 99%
“…Pressure waves at frequencies >15 Hz generally fade before reaching peripheral airways, while those at frequencies <10-15 Hz can penetrate much further into the lung periphery. 23 We used resistance at 5 Hz (R 5 ), 20 Hz (R 20 ), frequency dependence (R [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] ) as indicators of total, large, and small airway resistance, respectively; reactance at 5 Hz (X 5 ) was used as an index of the reactance of the overall respiratory system. [23][24][25][26] We also measured resonant frequency (F res ) and integrated area of low-frequency X (AX) as a sensitive measure of small airways obstruction.…”
Section: R T I C L E a R T I C L Ementioning
confidence: 99%